A STUDY OF COMMUNICATION STRATEGIES USED BY ENGLISH DEPARTMENT STUDENT - Wahyu Wigati; Lilia Indriani (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
Communication is one of the skills that must be mastered by English learners. When communicating in English, they need to know the strategies to achieve optimal communication. According to Dornyei (1995), a communication strategy is a strategy used by students who learn other languages to reduce their inability in language parts such as grammar and vocabulary. This study will explore the communication strategies used by the English Department Student. This study aims to determine the type and dominance of communication strategies used by the English Department Student. The object of this research is students from semester 5 of the English Department, Tidar University. This study uses a descriptive qualitative and quantitative approach. The researcher uses the questionnaire method to collect the data. The study finds that there are ten communication strategies used by English department students when they communicate in the English language. Those are message abandonment, topic avoidance, literal translation, borrowing or code-switching, approximation or generalization, word coinage, circumlocution, use of all-purpose words, self-repair or reconstructing, appeals for assistance. The researcher also finds that the dominant type of communication strategy used is the appeal for assistance.